Efektivitas Program Sistem Informasi Kesejahteraan Sosial (SIKS-Ng) dalam Mendukung Program SLRT dan Puskesos Dinas Sosial Provinsi Sulawesi Selatan - Andi Muhammad Asrandi T; Sari Apriliya Wati; Abdul Wahab; Alfian Alfian (CV. Publikasi Indonesia, 2022)
Poverty in South Sulawesi Province has experienced a significant decline with a rate of 1.01% from 2016 to 2018, where this decline is in line with the implementation of an Integrated Social Protection System called